Síntese de análogos do azul da prússia de manganês e sua aplicação como material ativo em eletrodos de supercapacitores - Victor Delfim dos Santos Fortunato (2024)
This study presents the development of a hybrid supercapacitor using a positive electrode composed of PbMnHCF@CNT, a Prussian Blue analogue, in combination with activated carbon as the negative electrode. Manganese hexacyanoferrate (MnHCF) was synthesized via the co-precipitation method. A sodium perchlorate electrolyte with a manganese chloride additive was used to increase the capacity retention and specific capacity of MnHCF. Subsequent partial substitutions of Mn with Zn and, for the first time as a battery electrode, Pb, were conducted to enhance the stability and conductivity of MnHCF, with the 50% Pb substitution proving most effective. Composites were developed with functionalized carbon nanotubes, with PbMnHCF@CNT exhibiting higher specific capacity and capacity retention after 1000 cycles. The most promising material, PbMnHCF050, was then studied as a positive electrode in a hybrid supercapacitor with an activated carbon negative electrode. The device showed an energy density of 7.3 Wh/kg at a power density of 57.4 W/kg, along with excellent cycling performance, demonstrating a 168% increase in cell capacitance after 1000 charge-discharge cycles. These results underscore the potential of these materials for applications in high-performance electrochemical supercapacitors.